EFFECT OF KARANGNUNGGAL BENTONITE ADDITION ON THE MECHANICAL STRENGTH OF CONVENTIONAL CERAMICS - Widodo Widodo; Solihin Solihin; Subari Subari (Indonesian Mining Journal, 2019)
Bentonite can be used as an additive in ceramics production. It can increase the thermal resistance and flexural strength of ceramics. Indonesia has a large amount of bentonite deposit. One of them is located in Karangnunggal, Tasikmalaya. The aim of this research is to study the effect of bentonite to increase the flexural strength of ceramic. The raw materials consisting of kaolin, feldspar, and quartz were used as raw materials in ceramics production. The weight percents of kaolin and quartz were fixed at 55 % and 20 %, whereas weight percents of feldspar and bentonite were varied at 25 %, 20 %, 15 %, 10 % and 0,5 %, 10 %, 15 %. The firing temperature was kept at 1,200 °C. Result of the experiment shows that the best composition to achieve the highest dry flexural strength at 254.70kg/cm2 is at 55 %kaolin, 20 % quartz, 15 % feldspar, and 10 % bentonite.